A Novel DDoS Attack-aware Smart Backup Controller Placement in SDN Design. (2020) - Haque, Muhammad Reazul; Tan, Saw Chin; Yusoff, Zulfadzli; Nisar, Kashif; Lee, Ching Kwang; Kaspin, Rizaludin; Chowdhry, BS; Ali, Sameer; Memon, Shuaib
No abstract available